2002
DOI: 10.1046/j.1526-4610.2002.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Young Italian Patients With Primary Headache

Abstract: Quality of life is compromised significantly in young patients with primary headache disorders. The questionnaire used in this study is a valid and reliable self-administered instrument that may facilitate clinical research in headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 34 publications
6
50
1
10
Order By: Relevance
“…Contrary to the authors' observations, previous studies in children with chronic headaches have reported impairment in school functioning in children with frequent headaches. 28,29 In a study of 122 adolescents with chronic daily headaches in Taiwan, more than half reported moderate to severe impairment of school performance. 20 A possible explanation of the authors' findings is the reported fear of failure and resultant overachievement in children with chronic headaches.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the authors' observations, previous studies in children with chronic headaches have reported impairment in school functioning in children with frequent headaches. 28,29 In a study of 122 adolescents with chronic daily headaches in Taiwan, more than half reported moderate to severe impairment of school performance. 20 A possible explanation of the authors' findings is the reported fear of failure and resultant overachievement in children with chronic headaches.…”
Section: Discussionmentioning
confidence: 99%
“…18 Literature shows some controversy in findings acquired from various studies on the quality of life of adolescents with migraine and its related factors. [19][20][21][22] Moreover, evidence about the adjusted association between migraine and the domains of quality of life (mental, social, environmental, and physical) among students, especially based on models such as linear regression, is rare. Therefore, it is necessary to do more studies in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing physical functioning (i.e., participation in physical activities, ability to perform physical tasks) is an important treatment goal 1 for adolescents with chronic pain, who as a group, demonstrate decreased physical function compared to healthy youth 2,3 . Physical function has been fairly extensively studied in youth with various pain conditions wherein youth or their parents have reported on perception of difficulty in the child's participation in developmentally appropriate activities due to pain 4,5 .…”
Section: Introductionmentioning
confidence: 99%